Sistem Pengolahan Data Pegawai dan Data Ormas/LSM Pada Badan Kesatuan Bangsa Dan Politik Kota Dumai Berbasis Web - Faradilla, Claura; Wahyuni, Deasy; Sofiyan, Amat (JOSTECH: Journal of Science and Technology, 2021)
Badan Kesatuan Bangsa dan Politik (KESBANGPOL) of Dumai City is one of the Regional Apparatus Organizations (OPD) in Dumai City. Previously, the processing of data at the KESBANGPOL agency has used several office application but there are still obstacles that occur in the processing process employee data and community Organization (ORMAS)/LSM which are usually in the from of written data and then processed using several office applications and then an information is generated about employees and ORMAS/LSM, one of the obstacles comes from the relatively long time spent and tend to be prone to errors (data redudancy). To solves this problem, a lecturer and employee data information system was created using methode of waterfall and using the PHP Programming language which can make it easier for employees and ORMAS/LSM registrant toprocess and access information regarding employe data and ORMAS/LSM data at the KESBANGPOL of Dumai City. This research result the processing of data at the Kesbangpol Dumai City that will simplify and accelerate data management wrongdoing, local regulations so that services is getting better.